The Responsibility of a Service Provider in Classical Roman Law (Теоретическая и прикладная юриспруденция)
The article is devoted to the responsibility of a service provider in Classical roman law. The author describes the main social and legal factores led to the changes in a service agreement in comparing with its structure in Preclassical period of roman law. Basing on fragments of classical juridical treatises he clariﬁes tthe responsibility for a breach of the main obligation tied with service providing as well as of the additional one going from caring for a customer’s thing. Exegesis to authentic sources combines with reviewing of traditional interpetations given by modern authors. The curring research showes the intrinsic interconnection between developing of formal legal relationships based on a contract of autonomic parties and rising of responsibility standards of a service provider. The appearing of an independent craftsman is caused by reglamention of the service agreement object. That object is regarded as physical efforts that will applied by a craftsman after certain period of time.